Taṭwīr al-māddah al-Ta’limiyyah li maharah al-Qira’ah ‘ala Asas al-Qiṣṣah al-Maḥalliyyah Li Ṭalabah al-Ṣaf al-Tsālits li al-Mutawassiṭah bi Ma’had al-Zahrah al-‘Asri Bireuen - Muhammad Amin (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Teaching and learning process constitutes a process which involves several substances purporting to achieve the aims having been planned. Teachers, students and curriculum are teaching and learning foundations. Books are part of a curriculum which plays an important role as a source of insight and information which are taught to students. Good books are books which are enjoyable and interesting to students. These efforts can be made by utilizing teaching media which induce enjoyable impressions which make books interesting. Therefore, the researcher wished to develop the contents of al-Qiraah al-Rasyidah by utilizing pictures. The researcher analyzed the problems and needs required to develop this book at the modern Islamic boarding school of Islamic Senior high school of Az-Zahrah. In this research, the researcher was willing to highlight the steps of how this book was developed, the obstacles faced during this investigation and the effectiveness of the output of this research. This research applied the method of developmental research. The approach utilized was qualitative in order to acquire the supporting data and the quantitative data were utilized to understand the output of this research. The tools used in this research were tests and interview and the data were processed with the correlation of t-test. This was conducted on the basis of the phases that have been determined in the methodology and this developmental research. Although there was an obstacle faced during this investigation, among others were the difficulties in finding illustrators and so on, al-Qiraah al-Rasyidah book which underwent the development process with pictures was effective in terms of student factors.